Plasmid-Encoded Toxin of Enteroaggregative Escherichia coli is Internalized by Epithelial Cells - Navarro-García, Fernando (American Society for Microbiology, 2001)
We have previously described a 104-kDa protein termed Pet (for plasmid-encoded toxin) secreted by some strains of enteroaggregative Escherichia coli (EAEC). Through an unknown mechanism, this toxin (i) raises transepithelial short-circuit current (Isc) and decreases the electrical resistance of rat jejunum mounted in the Ussing chamber, (ii) causes cytoskeletal alterations in HEp-2 cells and HT29/C1 cells, and (iii) is required for histopathologic effects of EAEC on human intestinal mucosa. Pet is a member of the autotransporter class of secreted proteins and together with Tsh, EspP, EspC, ShMu, and SepA proteins comprises the SPATE subfamily. Here, we show that Pet is internalized by HEp-2 cells and that internalization appears to be required for the induction of cytopathic effects. Evidence supporting Pet internalization includes the facts that (i) the effects of Pet on epithelial cells were inhibited by brefeldin A, which interferes with various steps of intracellular vesicular transport; (ii) immunoblots using anti-Pet antibodies detected Pet in the cytoplasmic fraction of intoxicated HEp-2 cells; (iii) Pet was detected inside HEp-2 cells by confocal microscopy; and (iv) a mutant in the passenger domain cleavage site, which prevents Pet release from the bacterial outer membrane, did not produce cytopathic effects on epithelial cells, whereas the release of mutant Pet from the outer membrane with trypsin yielded active toxin. We have also shown that the Pet serine protease motif is required to produce cytopathic effects but not for Pet secretion. Our results suggest an intracellular mode of action for the Pet protease and are consistent with we our recent report suggesting an intracellular mode of action for Pet (J. M. Villaseca, F. Navarro-García, G. Mendoza-Hernández, J. P. Nataro, A. Cravioto, and C. Eslava, Infect. Immun. 68:5920–5927, 2000).